DESIGN OF THE BEST SALES DETERMINATION SYSTEM IN BLITAR SOUVENIR SHOP USING SAW METHOD WITH WHITE BOX TESTING - Inna Qoryati; Abdi Pandu Kusuma (JOSAR (Journal of Students Academic Research), 2020)
O'o Dabli's shop is a shop that sells various kinds of typical Blitar products. The types of products sold by O'o Dabli's shop are various kinds of chili sauce, Blitar's typical snacks, drinks, Blitar's special crafts, Blitar's typical souvenir clothes, and so on. The products that are sold by this shop are predominantly selling types of food, there are various types of food here and if you want to make a purchase, sometimes we are confused to determine the type of product criteria. In a trading business, success in a company is inseparable from the role of strategy in sales. Improving the best service system in Blitar's Souvenir Shop is a process to recommend products to customers in a better way. So that service to customers is easier. The method used in the manufacture of a product sales system in a typical Blitar gift shop uses the saw method (simple additive weigthing). The reason for creating this system is because this system can provide benefits and advantages in decision makers to process data and information. This system uses white box testing or commonly referred to as glass box testing. This test is a philosophy that uses case test planning that uses a control structure that is described as part of designing a component device to produce test cases. The reason for creating this system is because this system can provide benefits and advantages in decision makers to process data and information. This system uses white box testing or commonly referred to as glass box testing. This test is a philosophy that uses case test planning that uses a control structure that is described as part of designing a component device to produce test cases. The reason for creating this system is because this system can provide benefits and advantages in decision makers to process data and information. This system uses white box testing or commonly referred to as glass box testing. This test is a philosophy that uses case test planning that uses a control structure that is described as part of the design of the component set to produce test cases.